Comparison of two techniques for target motion evaluation based on 4DCT images. (29th March 2012) - Lyatskaya, Yulia; Rehfeld, Kira; Kadam, Dnyanesh V.; Caglar, Hale; Allen, Aaron; Chin, Lee M.; Killoran, Joseph H.
Two techniques for target motion characterisation based on 4DCT images were evaluated: calculation of the conformality index and a technique based on image subtraction. The outputs for both techniques were shown to correlate with target displacement, indicating the applicability of these techniques for motion characterisation. While conformality index calculation requires target delineation (a time-consuming and subjective process), image subtraction is automatic and objective. In addition, the image subtraction method produces a visual representation of the areas where motion is present between different phases. The procedure has potential for automatic internal target volume definition for radiotherapy treatment purposes.